The effect of tax information dissemination, tax rates, and tax sanctions on compliance with annual tax return reporting of individual taxpayers (case study at Pandeglang primary tax service office) - Siti Halimah; Juitania Juitania (President University, 2022)
The lack of socialization of taxation provided to the community is one of the causes of low taxpayer compliance; people still perceive taxes as mandatory levies rather than community participation because they do not see real benefits for the state and society. The number of taxpayers showed is as followed the year of 2016 was 41,530 taxpayers, 2017 was 37,431 taxpayers, 2018 was 34,345 taxpayers, 2019 was 39,888 taxpayers, 2020 was 52,140 taxpayers. Those mean the outcome of processing related to Pandeglang Primary Tax Service Office taxpayers' compliance and It is clear that the realization rate of tax return submission is still low due to taxpayers' lack of awareness about reporting tax return. In the other hand Socializing taxation is one of the efforts made by the Pandeglang Regency Tax Service Office to increase taxpayers' knowledge and understanding of their rights and obligations. Thus, those made the researcher wanted to discover more about the problem.This study has been conducted at the Pandeglang Primary Tax Service Office, and the study period runs from August to December 2021. This study aims to determine the impact of taxation socialization, tax rates, and tax sanctions on individual taxpayers' annual tax return reporting compliance. This study used a quantitative approach with a sample of 384 taxpayers obtained through a random sampling technique. In this study, descriptive statistics and multiple linear regression are used to analyze data using the SPSS 25 computer software program. The four variables, taxation socialization, tax rates, and tax sanctions, affect the dependent variable, taxpayer compliance, according to the results of hypothesis testing.